Vad är globalisering? Sociologin utmanad (Sociologisk Forskning, 1999)
During the 1990s, the concept of ”globalization” has been established in sociology and in the social sciences more generally. This article argues that sociological theory and research on globalization constitutes a new discourse within sociology; challenging some of the cornerstones of established sociology. The aim of this article is to investigate, analyze and critically discuss this discourse. The article has three parts. The first part argues that two conceptual pairs, nation state/globalization and global/local, represent the two most central theoretical themes in globalization discourse. These themes - as well as globalization discourse in general - are centred around conceptions about new relations between social relations and power on the one hand, and territoriality on the other. In the second part it is argued that this discourse refers to world society as the main research object of ”the sociology of globalization”. The third partdiscusses some aspects of the critique of established sociological theories and research strategies articulated in sociological theories of globalization. The conclusion argues that globalization discourse in some respects needs more empirical grounding and further theoretical development. However, its challenge must be taken seriously, not the least because it points to, and present meaningful analyses of, a number of present-day phenomena that are not so easily grasped by established sociological perspectives.